The Effect of Chlorhexidine on Resin-Dentin Bond Strength: One-Step Versus Two-Step Application - Dardeer, Faisal. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Pediatric Dentistry.; Advisor: Cheen Loo.; Committee: Yoon Kang, Driss Zoukhri, and Sarah Pagni.; Keyword: Dentistry.